“Estrategias de enseñanza basada en el pensamiento crítico y la lectura” - Taco Amaya, Myrian Paulina (2022)
Educational process presents changes that demand new competences to answer the present society needs which should be focused on the students’ critical skills development in order to train them as critical and reflexive beings as a part of their integral growing. Thus, teachers should apply new teaching strategies based on the critical thinking in the pedagogical process, so that they contribute the cognitive, procedural and attitudinal skills meaningfully. Teachers in their pedagogical process have focused the class in traditional practices for this reason they are considered as the unique knowledgment possessors. In addition, applied strategies do not contribute to critical thinking development, consequently students learning is rote, receptive and mechanical. The objective of this research is to propose teaching strategies based on critical thinking through unpublished literary texts for reading development in Language and Literature area in fifth grade of General Basic Education, in Latacunga canton, Cotopaxi province. The methodology was based on interpretative approach since it allowed to understand real social context in its suitable nature. This search was focused on qualitative design, which process follow these stages: preparatory, field and informative analytics, also is documentary and descriptive. It was applied inductive method technique is interview for teachers, the collected information showed the real problems in the educative context. The achieved results are original literacy texts based on three stories, three fables, ten tongue-twisters, ten sayings, and fourteen phrases with positive values. Furthermore, they include worksheets for each literary text, which provide praxis reading and students’critical thinking development. Therefore, this project contributes to reasoning development by means of new material, that shows the educational practice creativity, thus it motivates students to reading through reflection, comprehension, interpretation, and evaluation, these skills promote critical thinking development in their learning process.